PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN FUSSION FOOD DI SMK NEGERI 2 BUKITTINGGI - Mardhatillah, Mardhatillah; Baidar, Baidar; Yulastri, Asmar (Journal of Home Economics and Tourism, 2016)
The purpose of this study was to determine the validity and practicalities of multimedia. This type of research or development Research and Development using three stages of four stages of the development model of the 4-D Models. Subjects of this study consisted of 5 people validator, and to test the practicalities conducted by two teachers and 30 students of class XII SMK Negeri 2 Bukittinggi. Data collection techniques in this study using a questionnaire and analyzed by descriptive analysis using a percentage formula that includes analysis of the validity and practicalities. The results showed that for design validation obtained a value of 0.86 and a validation of the material / content obtained a value of 0.82 with a valid category. As for the practicalities of test values obtained with an average score of 91.56% in a very practical categories of teachers and of students obtained an average score of 86.03% with a very practical category. Based on the above it can be concluded that interactive multimedia is valid and very practical for use as a media on subjects Fussion Food.Keywords: Development, Interactive Multimedia, Fussion Food